The Effect of Digital Financial Literacy, Fintech Use, and Financial Self- Efficacy on Generation Z Financial Management Behavior in Lhokseumawe - Muhammad Multazam; Sutan Febriasyah; Ismuhadi; Yusnidar; Maulana Majied Sumatrani Saragih (Journal of Economics, Management, Development, and Education, 2026)
This study examines the influence of digital financial literacy, fintech use, and financial self-efficacy on the financial management behavior of Generation Z in Lhokseumawe City. The issue is relevant because young consumers are intensive users of mobile banking, e-wallets, QRIS, paylater, and investment applications, while digital access does not always produce disciplined financial decisions. This research applies a quantitative explanatory design with a survey of Generation Z respondents who live in Lhokseumawe and use at least one fintech service. Data will be collected using a Likert-scale questionnaire and analyzed through validity testing, reliability testing, descriptive statistics, and SEM-PLS. Digital financial literacy is measured through knowledge, security awareness, risk evaluation, and the ability to compare digital financial products. Fintech use is measured through frequency, diversity, perceived usefulness, and transaction habits. Financial self-efficacy is measured through confidence in budgeting, saving, debt control, and resisting impulsive spending. The proposed model expects all independent variables to positively affect financial management behavior. This study contributes to digital financial education and youth financial policy in local urban contexts.